Tobacco use and the risk of catastrophic healthcare expenditure (2018)
BACKGROUND: Tobacco consumption increases the chance that an individual will suffer from illhealth. Financial cost associated with increased demand for medical care can be substantial and catastrophic, especially for households in the lowest income stratum. This paper extends what is known about the poverty impact of tobacco use by estimating the increased risk of incurring higher catastrophic health expenditure because of tobacco consumption. METHODS: The data for the study were drawn from the Harmonized Nigerian Living Standard Survey (HNLSS) conducted in 2009/2010 by the National Bureau of Statistics. Three log-linear models of health expenditures were used to predict the health expenditure attributable to tobacco consumption. The incidence of catastrophic health expenditure (CHE) was estimated using the standard 40-percent threshold of household total nonfood expenditure. RESULTS: Based on the three log-linear regression models, smokers had higher health expenditure compared to non-smokers (by 43.91%, 33.23% and 41.51%). Excess average health expenditure attributable to tobacco use was the highest among moderately poor smokers (Nigerian national currency Naira (NGN) 37,734.90 (USD251)) and the lowest among non-poor smokers (NGN 7,819.78 (USD52)). In addition, extremely poor smokers incurred higher medical expenditure attributable to tobacco use compared to non-poor smokers. Among the non-poor households, 23.87% experienced CHE in the rural areas and 13.62% in the urban ones. Accounting for the predicted excess medical expenditure among smokers, there was a 3.11% increase in the burden of CHE among households living in rural location. Overall, excess medical expenditure associated with tobacco use increased the incidence of CHE among households. CONCLUSION: Essentially, smoking will aggravate the financial hardship of households because of higher burden of CHE in the short and long run. Therefore, healthcare policymakers in Nigeria can reduce the excessive financial burden attributable to smoking by developing policies that curtail tobacco consumption. Evidence provided in this study supports this.